PWE-356 Solitary intra-abdominal metastasectomy for malignant colorectal cancer; a case series. (22nd June 2015) - Wright, H; Feldman, M
Abstract : Introduction: Patients developing intra-abdominal peritoneal, wound or metachronous lymph node metastases after colorectal cancer surgery have been treated as having inoperable stage IV disease. However modern developments in combination chemotherapy and surgery has led patients with limited liver and lung metastases to have 30% 5 year and 20% 10 year survival. 1 There are no international or national guidelines to assist in the identification of patients who may benefit from an abdominal metastatectomy. 2 This paper reviews the outcomes we have achieved with surgery for patients with a single abdominal metastasis in whom a complete surgical resection is expected. Method: Our prospective database was searched for patients undergoing surgery for recurrent disease since 2000. Patients having further bowel resection due to anastamotic recurrence, pelvic extenteration (in tertiary units) or excision of Krukenberg tumours were excluded. All patients underwent CT preoperatively, with a 3–6 month period of observation to ensure they did not have rapidly progressive disease and those presenting after 2007 had PET scanning. Results: 7 patients fulfilled the criteria and underwent surgery with the aim of achieving an R0 resection. Conclusion: When R0 resection is achieved metastasectomy can be associated with long term survival. With careful patient selection and MDT consideration, surgery to remove isolated metastases should be considered. Disclosure of interest: None Declared. References: Office for National Statistics, Cancer Survival by NHS England Area Team, Adults diagnosed 1997-2012, followed-up 2013, 2014, www.ons.gov.uk Mahmoud N, Dunn KB. Metastasectomy for stage IV colorectal cancer. Dis Colon Rectum . 2010 Jul;53(7):1080-92. doi:10.1007/DCR.0b013e3181dcadbc